2004
DOI: 10.1038/sj.emboj.7600334
|View full text |Cite
|
Sign up to set email alerts
|

Morphine induces terminal μ-opioid receptor desensitization by sustained phosphorylation of serine-375

Abstract: Morphine is a poor inducer of l-opioid receptor (MOR) internalization, but a potent inducer of cellular tolerance. Here we show that, in contrast to full agonists such as [D-Ala 2 -MePhe 4 -Gly-ol]enkephalin (DAMGO), morphine stimulated a selective phosphorylation of the carboxyterminal residue 375 (Ser 375 ). Ser 375 phosphorylation was sufficient and required for morphine-induced desensitization of MOR. In the presence of full agonists, morphine revealed partial agonistic properties and potently inhibited MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
220
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(236 citation statements)
references
References 29 publications
12
220
4
Order By: Relevance
“…1B). Consistent with previous observations in other heterologous expression systems (3,10), morphine induced significantly less robust phosphorylation of this residue than DAMGO regardless of genotype, thus demonstrating that the agonist-dependent differences in MOR phosphorylation at Ser-375 are preserved in the absence of ␤-arrestins.…”
Section: Generation Of Mor-expressing Mef Lines-tosupporting
confidence: 79%
See 4 more Smart Citations
“…1B). Consistent with previous observations in other heterologous expression systems (3,10), morphine induced significantly less robust phosphorylation of this residue than DAMGO regardless of genotype, thus demonstrating that the agonist-dependent differences in MOR phosphorylation at Ser-375 are preserved in the absence of ␤-arrestins.…”
Section: Generation Of Mor-expressing Mef Lines-tosupporting
confidence: 79%
“…Subsequent studies have demonstrated that morphine's attenuated ability to promote MOR internalization is a consequence of morphine being less effective at promoting MOR phosphorylation and ␤-arrestin recruitment compared with other opioids. In fact, overexpression of GRK2 in cells can augment morphine-induced MOR phosphorylation, ␤-arrestin2 recruitment, and internalization (3,9,10). These data also suggest that in addition to the ligand, MOR regulation and trafficking are also dependent on the complement of intracellular interacting proteins expressed in residence with the receptor.…”
mentioning
confidence: 59%
See 3 more Smart Citations